AKUNTANSI MEMBANGUN DESA DI DESA AIR ANYIR KECAMATAN MERAWANG KABUPATEN BANGKA - Desy Yuliana Dalimunthe; Ineu Sulistiana; Abu Nizarudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2016)
This KKN activity aims to make efforts to learn accounting for the village. It is hoped that accounting is not a difficult and difficult thing to learn. But in learning. However, village officials, especially those who handle village funds, must be equipped intensively through experts in the field of accounting who provide assistance. This KKN activity was carried out by Bangka Belitung University students from various disciplines totaling 35 students, which began with the release of students on July 19, 2016 and ended with the pick-up of students at the KKN location on August 24, 2016. The main programs of this KKN activity include: 1) Socialization of the Village Law, 2) Socialization of Assistance and Preparation of Medium Term Development Plan (RPJM), 3) Socialization and Entrepreneurship Training for UMKM, 4) Assistance and Preparation of Village Accounting and Finance and 5) Assistance in Preparing Village Financial Reports. The results of this KKN activity include KKN students, especially those who have received debriefing on Village Accounting, can become Agents of Change in educating the Nation's Life, especially the Village Apparatus. educate the Nation's Life, especially the Village Apparatus that handles finances and the preparation of village financial reports, especially in the Village of financial reports, especially in Air Anyir Village, Merawang District, Bangka Regency.